2007
DOI: 10.1007/s10681-007-9448-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, characterization and expression of two rapeseed (Brassica napus L.) cDNAs orthologous to Arabidopsis thaliana phenylalanine ammonia-lyase 1

Abstract: Phenylalanine ammonia-lyase (PAL) plays important roles in determining flavonoid-and lignin-related traits. Two PAL full-length cDNAs, BnPAL1-1 and BnPAL1-2, were isolated from Brassica napus. BnPAL1-1 is 2460 bp encoding a 722-aa protein, while BnPAL1-2 is 2396 bp encoding a 719-aa protein. BnPAL1-1 shares 86.8% nucleotide identities and 94.9%/97.0% identities/positives at protein level to BnPAL1-2. NCBI BLAST, pairwise alignment and preferential amino acid analysis indicated that they are orthologs of Arabid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
(89 reference statements)
0
9
0
Order By: Relevance
“…In previous studies, we isolated and characterized the key enzyme loci for F3'H and PAL1 and the regulatory loci TTG1 and TT2 from B. napus. Interestingly, we found that these genes showed no or limited downregulation in the yellow seed line L2 bred by our group Lu et al 2007;Wei et al 2007;Ni et al 2008). …”
Section: Introductionmentioning
confidence: 65%
“…In previous studies, we isolated and characterized the key enzyme loci for F3'H and PAL1 and the regulatory loci TTG1 and TT2 from B. napus. Interestingly, we found that these genes showed no or limited downregulation in the yellow seed line L2 bred by our group Lu et al 2007;Wei et al 2007;Ni et al 2008). …”
Section: Introductionmentioning
confidence: 65%
“…Moreover, several key loci isolated from B . napus by our group, such as F3'H, PAL1, TTG1 , and TT2 , showed no or limited down-regulation in the yellow-seeded lines (Wei et al, 2007; Xu et al, 2007; Ni et al, 2008; Lu et al, 2009). Based on a marker closely linked with a major QTL for seed fiber and color in B .…”
Section: Introductionmentioning
confidence: 77%
“…Hence, identifying candidate genes by cloning Brassica TT genes involved in the flavonoid biosynthetic pathway and conducting comparative studies of these genes is a reasonable approach, and many homologs of these genes have also been identified in B. napus (Wei et al, 2007; Xu et al, 2007; Ni et al, 2008; Chai et al, 2009; Lu et al, 2009; Chen et al, 2013). However, little is known about the mechanism underlying seed color formation in B. napus .…”
Section: Discussionmentioning
confidence: 99%
“…napus (Theander et al, 1977; Marles and Gruber, 2004; Akhov et al, 2009; Qu et al, 2013), and dozens of homologous genes in the B . napus flavonoid biosynthesis pathway have been cloned and characterized (Wei et al, 2007; Xu et al, 2007; Ni et al, 2008; Akhov et al, 2009; Auger et al, 2009; Chai et al, 2009; Lu et al, 2009; Chen et al, 2013). Prior to this study, no comprehensive analysis of the flavonoid biosynthesis pathway had been conducted in B. napus .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some homologs of genes involved in flavonoid biosynthesis have been cloned and characterized in B . napus (Wei et al, 2007; Xu et al, 2007; Ni et al, 2008; Akhov et al, 2009; Auger et al, 2009; Chai et al, 2009; Lu et al, 2009; Chen et al, 2013). These results provide a foundation for further studies of the molecular and regulatory mechanisms underlying seed coat color formation in B. napus .…”
Section: Introductionmentioning
confidence: 99%